Representation of the Meaning of Awe in the Lyrics of the Song “From Another Planet” by Sal Priadi (Semiotic Analysis of Ferdinand De Saussure) - Ssimanullang, Sascia Eunike Maria; Sadiyyah, Zulfanida Nurul; Gamaska, Wika; Watratan, Martharia Anselma (Sinergi International Journal of Communication Sciences, 2023)
Music or lyrics are an inseparable element in human life since ancient times until now, because song lyrics have a deep emotional impact on listeners who feel connected to the lyrics of the song. So that many songwriters express a feeling, anxiety, or social reality they see, through a song lyric. The Representation of the Meaning of Amazement in the lyrics of the song “From Another Planet” by Sal Priadi”, aims to represent the meaning of amazement in the lyrics of the song using semiotic theory. The semiotic theory used to dig deeper into the lyrics of the song “From another planet” is Ferdinand De Saussure’s semiotic theory, which aims to find out how the signifier and signified in the song lyrics. Songs like “From another planet” not only convey complex feelings but also have deep meaning. The results of this study suggest that the song “From another planet” describes a feeling that arises when one feels overwhelmed or admire, when the person’s presence brings out unique, different from the previous one, or gives new color to the song writer’s life.